2002
DOI: 10.1063/1.1432698
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic instability of a high magnetic shear layer with a finite curvature radius

Abstract: This article deals with the magnetohydrodynamic instability of a thin layer which is characterized by a high magnetic shear, a constant curvature radius, and a plasma velocity shear. The magnetic field and the plasma parameters are considered to be piecewise constant inside the layer and in the regions adjacent to the layer. The plasma parameters and the magnetic field are assumed to obey the ideal incompressible magnetohydrodynamics. Fourier analysis is used to calculate small perturbations of the magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…For a nonlocal analysis with smooth profiles, it is rather complicated to take into account a shear angle. However, effects of a finite shear angle have been studied previously by Arshukova et al (2002) for the particular case of a uniform layer with enhanced plasma pressure which is separated by two tangential discontinuities. The interchange instability growth rate was obtained by Arshukova et al (2002) as a function of the magnetic shear angle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a nonlocal analysis with smooth profiles, it is rather complicated to take into account a shear angle. However, effects of a finite shear angle have been studied previously by Arshukova et al (2002) for the particular case of a uniform layer with enhanced plasma pressure which is separated by two tangential discontinuities. The interchange instability growth rate was obtained by Arshukova et al (2002) as a function of the magnetic shear angle.…”
Section: Discussionmentioning
confidence: 99%
“…For our instability analysis, we use the profiles of the magnetic field and plasma parameters which are obtained from the MHD model of a nonsteady solar wind flow around the magnetosphere (Erkaev et al, 2002) modeled as a paraboloid of revolution. This model is similar to that applied previously to a steady solar wind flow around the Earth's magnetosphere , or the nonsteady flow around a magnetic cloud .…”
Section: A Current Layer Moving From the Bow Shock Towards The Magnetmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Kelvin's circulation theorem, which ensures the conservation of the circulation, does not hold in MHD flows. Thus, the previous works on the theoretical analysis have been limited to either the linear stability theory (Gerwin, 1967, Chen and Hasegawa, 1974, Arshukova et al, 2002, Ilin et al, 2003, Cao et al, 2008 or the weakly nonlinear analysis (Hunter and Thoo, 2011). However, it is found that when the magnetic field does not initially possess the normal component to the interface, the concept of vortex sheet model can be extended naturally to the currentvortex sheet model in MHD flows including the nonlinear regime.…”
Section: Introductionmentioning
confidence: 99%
“…This magnetic tension forms specific types of plasma flow stream lines near the ionopause, which are orthogonal to the magnetic field lines. This process favors the appearance of Kelvin-Helmholtz and interchange instabilities that can detach ionospheric plasma in the form of detached ion clouds from a planet (Biernat et al, 1999;Arshukova et al, 2002).…”
mentioning
confidence: 99%